The Impact That Different Types of Organizational Cultures Have on the Adjustment of Self-Initiated Expatriates - Kumpikaitė-Valiūnienė, Vilmantė; Žičkutė, Ineta; Banevičienė, Irma; Gao, Junhong; Torres, Denisse (Frontiers in Psychology, 2022)
This paper investigates the adjustment of self-initiated expatriates, with a particular emphasis on organizational culture. One hundred and twenty-five self-initiated expatriates around the globe participated in the online survey. We examined the impact that organizational culture has on self-initiated expatriate work and non-work-related adjustment using multiple linear regression analysis. Four types of organizational culture (clan, adhocracy, market, and hierarchy) were explored. The results revealed that Clan culture has a positive effect on the work and non-work-related adjustment of self-initiated expatriates.